Boosting High School Students' Speaking Proficiency with Gemini AI - Marpaung, Syafaruddin (English Journal Antartika, 2024)
Abstract: This study investigates the impact of Gemini AI on improving speaking proficiency among 30 high school students using Classroom Action Research (CAR) with a mixed-methods approach. The study observed progressive improvements in speaking proficiency over three iterative cycles, with students’ average scores rising from 65 in the first cycle to 85 by the third cycle. These gains were reflected in enhanced fluency, vocabulary, and confidence. Gemini AI provided personalized speaking practice and real-time feedback, leading to increased engagement and adaptive learning. The study concludes that integrating AI into speaking classes can enhance language proficiency through iterative feedback and adaptation. Keywords: Boosting, High School Students, Speaking Proficiency, Gemini AI